2008
DOI: 10.1016/j.ygeno.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted transcriptional regulation of the murine intestinal mucus layer by endogenous microbiota

Abstract: The intestinal mucus layer and endogenous microbiota are strongly intertwined and this contributes to the maintenance of the epithelial barrier and ultimately of gut homeostasis. To understand the molecular foundations of such relationship, we investigated if the nature of the microbiota transcriptionally regulates mucus layer composition in vivo. We found that the expression of mucins 1 to 4 and trefoil factor 3 was down-regulated in the ileum and colon of conventional and reconventionalized mice compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…Seminal work showed that, in germ-free rodents, the mucus layer is reduced by half and is less stable,114 and has an altered glycosylation profile compared with conventional hosts 18 41. The use of cDNA microarray analysis has shown the participation of a well-established intestinal microbiota in regulation of the gut mucus layer and composition 65. It has been suggested that the resident microbiota can affect goblet cell dynamics and mucin composition directly, by the release of bioactive factors, and indirectly by activating host cells 7 41.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal work showed that, in germ-free rodents, the mucus layer is reduced by half and is less stable,114 and has an altered glycosylation profile compared with conventional hosts 18 41. The use of cDNA microarray analysis has shown the participation of a well-established intestinal microbiota in regulation of the gut mucus layer and composition 65. It has been suggested that the resident microbiota can affect goblet cell dynamics and mucin composition directly, by the release of bioactive factors, and indirectly by activating host cells 7 41.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that a variety of microbial products can stimulate increased production of mucins by mucosal epithelial cells 61–63. Also, germ-free mice exhibit changes in mucin gene expression, mucus composition and mucus secretion in response to intestinal bacteria or host-derived inflammatory mediators 64 65. Therefore, it can be surmised that alterations in mucus secretion and composition, including mucin glycosylation, represent important mechanisms for unfavourably changing the niche occupied by a mucosal pathogen.…”
Section: Bacterial Interactions With Mucinsmentioning
confidence: 99%
“…Outstandingly, gut and root bacteria modify gene expression in animal (138,139) and plant (140) hosts, respectively. Gut gene expression is also modified by probiotics (113) that modify gut bacterial gene expression as well (141).…”
Section: Similar Bacterium-host Interactions In Guts and Rootsmentioning
confidence: 99%
“…One of the mechanisms underlying this host-microbe mutualistic relationship is the reciprocal impact of host and microbial cells on each other's gene expression programs 6,7. In particular, the endogenous microbiota acts as an environmental factor impacting the expression of thousands genes in the host epithelium 8,9, and this is a function of its composition 9,10. However, the impact of the microbiota on the intestinal gene expression signature at the messenger RiboNucleic Acid (mRNA) level may have thus far been under-evaluated due to a lack of studies linking gut microbiota to epigenetic changes in gene expression particularly, via micro-RiboNucleic Acids (miRNA).…”
Section: Introductionmentioning
confidence: 99%